DNA detection of Helicobacter pylori in saliva of patients with low salivary pH - Rahman, Lajan Qasim; Rahman, Asma Qasim; Bakir, Amin Aziz; Muhamadamin, Rebin Ali; Khudhur, Pinar Khalid (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: One of the well-organized diagnostic methods of Helicobacter pylori (H. pylori) infection is bacterial DNA detection in saliva using polymerase chain reaction (PCR). However, a wide range of factors is present in human saliva that could hinder detection efficiency. One of these factors seems to be the pH of saliva, which is investigated in this study as to whether its variation could have any effects on H. pylori DNA presence in the saliva of infected patients. Methods: Saliva samples of 89 H. pylori-infected Patients were collected and measured for pH levels. The DNA of H. pylori was extracted from the saliva of patients and then quantified directly by Real-time PCR. One Way ANOVA and Linear Regression tests were performed to determine the effect of pH on the detection of H. pylori DNA in the saliva. Results: 58% of samples were PCR positive (17% high, 19% medium, and 22% low titer), and no DNA was detected in 42% samples. There was no significant association between the age of patients and the detection of DNA (P = 0.98). A statistically significant difference in pH level was found between negative and positive PCR samples. Calculation of linear regression of DNA copy numbers and independently increasing pH showed R2 = 0.041. Conclusion: The ability to detect H. Pylori DNA was generally confined to pH of 5.5 to 7.5 with an apparently reduced detectability at above neutral pH of saliva. However, pH variation from 5.5 to 7.5 did not determine the levels of detected DNA of H. pylori in saliva.